House held up by trees : not far from here, I have seen a house held up by the hands of trees. This is its story - Kooser, Ted (Candlewick Press, 2012)
Built on a treeless yard by a family who cleared away all the sprouting trees on the property, a house is eventually abandoned and left to deteriorate on a lot that is gradually overrun by wild trees, in a poignant tale of loss, change, and nature's quiet triumph.